GAMBARAN PROFIL LIPID PADA PENDERITA PENYAKIT JANTUNG KORONER DI RUMAH SAKIT UMUM DAERAH Dr. H. CHASAN BOESOIRIE TERNATE - Stenly Mala; Andi Sitti Nur Afiah; Maryam Sun Dunggio (Kieraha Medical Journal, 2020)
Cardiovascular disease is the major cause of death in the world. The most common type of cardiovascular disease that causes death in the world is coronary heart disease. Coronary Heart Disease (CHD) is a cardiovascular disease caused by blockages in blood vessels so that blood flow to the heart becomes obstructed. The CHD process initially begins with people's behavior and lifestyle leading to dyslipidemia. Dyslipidemia is abnormal blood lipids including an increase in level of total cholesterol, triglycerides, LDL cholesterol and a decrease in HDL cholesterol levels. The study determines the description of the lipid profile in patients of CHD. This is descriptive study using secondary data in the form of medical records of CHD patients at Dr.H.Chasan Boesoirie Ternate Hospital in the period of 2018-2019. The population of this study is all data of CHD patients and it involves 131 patients as sample of the study, 30 of them meet the inclusion criteria and 101 of them are exclusion criteria. The results reveals that the highest number of CHD patients is 36.7% of age group 61-70 years, 60% of male, 66.7% of normal total cholesterol level, 86.7% of normal triglyceride levels, 53.3% of high LDL cholesterol and low HDL cholesterol in men by 33.3% and women by 26.7%. It can be concluded that the description of the lipid profile in CHD patients has normal total cholesterol and triglyceride levels, high LDL cholesterol and low HDL cholesterol.Keywords: Coronary Heart Disease, HDL, LDL, Total Cholesterol, Triglyserides